PENYAJIAN KEANEKARAGAMAN MAKROZOOBENTOS DI SUNGAI BEREMBANG DALAM MEDIA PEMBELAJARAN ENSIKLOPEDIA PADA SUBMATERI INVERTEBRATA KELAS X SMA - Pristalika, Yunike; Tenriawaru, Andi Besse; Candramila, Wolly (Jurnal Pendidikan Biologi, 2022)
Abstrak. The development of printed media in the form of an encyclopedia was carried out in this study to become a learning solution in schools that still have less IT facilities. Sub material of Invertebrate is one of the materials that is considered difficult because it contains a lot of material and unfamiliar terms, while the lesson hours are few. The inclusion of macro-zoo-benthos diversity in the encyclopedia media for use in schools located close to the aquatic ecosystem is believed to be able to provide more rich concepts for teachers to teach to their students. The success of developing the encyclopedia media as obtained in this study is expected to be able to answer the above problems while at the same time providing a variety of media for the school.Abstract. The development of printed media in the form of an encyclopedia was carried out in this study to become a learning solution in schools that still have less IT facilities. Sub material of Invertebrate is one of the materials that is considered difficult because it contains a lot of material and unfamiliar terms, while the lesson hours are few. The inclusion of macro-zoo-benthos diversity in the encyclopedia media for use in schools located close to the aquatic ecosystem is believed to be able to provide more rich concepts for teachers to teach to their students. The success of developing the encyclopedia media as obtained in this study is expected to be able to answer the above problems while at the same time providing a variety of media for the school.